2007
DOI: 10.4161/cbt.6.12.4961
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of glyoxalases gene expression in response to testosterone in LNCaP and PC3 human prostate cancer cells

Abstract: Glyoxalase system, a ubiquitous detoxification pathway protecting against cellular damage caused by potent cytotoxic metabolites, is involved in the regulation of cellular growth. Aberrations in the expression of glyoxalase genes in several human cancers have been reported. Recently, we described a possible regulatory effect by estrogens on glyoxalase genes in human breast cancer cell lines. This result, along with those ones regarding changes in glyoxalases activity and expression in other human hormoneregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Indeed, we found that Glo2 role in prostate carcinogenesis is dependent on AR signaling. Therefore, here we demonstrated for the first time that AR is not just an upstream regulator of Glo2 but acts as a key player in the mechanism of prostate tumorigenesis driven by Glo2. This was supported by IHC analysis that showed a significant positive correlation between Glo2 and AR expression in PCa tissues.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Indeed, we found that Glo2 role in prostate carcinogenesis is dependent on AR signaling. Therefore, here we demonstrated for the first time that AR is not just an upstream regulator of Glo2 but acts as a key player in the mechanism of prostate tumorigenesis driven by Glo2. This was supported by IHC analysis that showed a significant positive correlation between Glo2 and AR expression in PCa tissues.…”
Section: Discussionmentioning
confidence: 68%
“…In PCa, we and others have consistently demonstrated a major role of Glo1 in the progression of this neoplasia rather than its genesis . While the role of Glo1 has been extensively investigated, very little is known about Glo2, including its role in the glyoxalase system, and its physiological significance in human cancers, including PCa . In the present study, we investigated the role of Glo2 in prostate tumorigenesis, and, consequently, its potential use as marker in the early diagnosis of PCa.…”
Section: Introductionmentioning
confidence: 88%
“…In particular, we showed that Glo2 was selectively expressed in PCa but not in the luminal compartment of the adjacent benign epithelium consistently in all the examined cases (n = 20). Moreover, we demonstrated that Glo2 expression in malignant prostate cells was dependent on androgen receptor, in line with another previous exploratory study by our group [35], and was aimed at stimulating cell proliferation and eluding apoptosis through a mechanism involving the p53-p21 axis. Hence, our results demonstrated for the first time a role of Glo2 in prostate tumorigenesis and the associated mechanism.…”
Section: Glo2supporting
confidence: 90%
“…Nevertheless, RCC recurs in 20-40% of patients after resection, which is associated with a worse tumor stage and grade [9]. To further exacerbate the situation, at least some malignancies of the urinary tract are age-related, therefore, it is very plausible Glo1 activity can be regulated through several mechanisms including gene expression regulation [21,26,35,36] and post-translational modifications such as phosphorylation, NO-mediated modification and glutathionylation [21,[38][39][40][41]. Glo2 expression can be upregulated by the transcription factors p63 and p73 [42], steroid hormones [35], androgen receptor [37] and PTEN/PI3K/AKT/mTOR signalings [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation